Possibilities to Increase the Competitiveness of Lithuanian Apparel and Textile Industry - Vaiginienė, Erika; Miškinis, Algirdas; Kasnauskienė, Gindra (Ekonomika, 2006)
The purpose of the article is to analyze the situation of the Lithuanian apparel and textile industry and to propose means for increasing its competitiveness. By using M. Porter’s“diamond” model, primary and secondary data, we analysed the competitiveness of the Lithuanian apparel and textile industry. The analysis showed that the competitiveness of the Lithuanian apparel and textile industry is still very much dependent on the cheap Lithuanian labor force: there i, a lack of systematic mindset towards the development of the industry and employment of it, unused opportunities.The article describes the state of the Lithuanian apparel and textile industry after one year of the liberalized international trade of the industry. The analysis was done by using data received from Eurostat, Euratex and the Lithuanian Statistical Department. Primary data were collected from interviews and a questionnaire survey.Lithuania is one of the most specialized countries in the production of apparel and textile among the members of the European Union. Statistical data show that the apparel and textile industry ha an important impact on the Lithuanian economy and social life even after the liberalization of textile import at the beginning of 2005. In 2005 it comprised 8.3% of the total manufacturing industry output, its exported output reaching 9.8% of the total Lithuanian export, and there were about 51000 employees in the industry.The article shows that the Lithuanian apparel and textile industry is on its crossroad when the former competitive advantages have to be changed by the new ones. Efficient labor force and new technologies have to replace the cheap labor force, so there is a great need for new mindsets and financial resources. Surveys have shown that companies use bank loans or their own financial resources for the renovation. This means that the renovation of the Lithuanian textile industry can be facilitated by providing more information about the possibilities of preferential loans and by revoking the taxation of investment in Lithuania. The competitive advantages of the Lithuanian apparel and textile industry are the well developed infrastructure, the growing purchasing power and evolving needs of consumers, and natural resources such as linen and wool which can be used for the development of home and technical textile production in Lithuania.Nowadays the most important competitive advantage of the Lithuanian apparel and textile industry is the proximity to Scandinavian and other European Union countries, which allows to identify the needs and to serve them much quicker in comparison with the third countries (China, India, etc.).Although, managers of the Lithuanian apparel and textile companies perceive themselves as working in an open market already, and their approach to competitiveness is quite qualified, there are still lots of managerial problems. Generally, there is a lack of insight and no systematic perception of the industry, which are very important for creation of common competitive business systems in the industry. That is why we propose to Lithuanian Ministry of Economy to establi.h a group of consultants in cooperation with the Association of Lithuanian Apparel and Textile Industry and different educational institutions. The group would work with all those institutions and businesses in order to solve different kinds of problems and challenges. We propose to establish a fund of reorganization, the aim of which would be to work with hard-standing companies that need reorganization or closure.And finally, there are such opportunities as specialization in home textile, technical textile and production of wool articles for the Lithuanian apparel and textile industry. Those articles would find their markets in Scandinavia and other European Union countries where Lithuania has an advantage of market proximity.